Influence of different methods to determine maximum heart rate on training load outcomes in basketball players - Berkelmans, D. M.; Dalbo, V. J.; Fox, J. L.; Stanton, R.; Kean, C. O.; Giamarelos, K. E.; Teramoto, M.; Scanlan, A. T. (The Journal of Strength and Conditioning Research, 2018)
The summated-heart-rate-zones (SHRZ) approach uses heart rate (HR) responses relative to maximum HR (HRmax) to calculate the internal training load (TL). Age-predicted, test-derived, and session-based approaches have all been used to determine HRmax in team sports. The purpose of this study was to determine the effects of using age-predicted, test-derived, and session-based HRmax responses on SHRZ TL in basketball players. Semiprofessional, male basketball players (N = 6) were analyzed during the preparatory training phase. Six age-based approaches were used to predict HRmax including Fox (220 - age); Hossack (206 - [0.567 × age]); Tanaka (208 - [0.7 × age]); Nikolaidis (223 - [1.44 × age]); Nes (211 - [0.64 × age]); and Faff (209.9 - [0.73 × age]). Test-derived HRmax was taken as the highest HR during the Yo-Yo intermittent recovery test (Yo-Yo IRT), whereas session-based HRmax was taken as the higher HR seen during the Yo-Yo IRT or training sessions. Comparisons in SHRZ TL were made at group and individual levels. No significant group differences were evident between SHRZ approaches. Effect size analyses revealed moderate (d = 0.60-0.79) differences between age-predicted, test-derived, and session-based methods across the group and individually in 2 players. The moderate differences between approaches suggest age-predicted, test-derived, and session-based methods to determine HRmax are not interchangeable when calculating SHRZ. Basketball practitioners are encouraged to use individualized HRmax directly measured during field-based tests supplemented with higher HR responses evident during training sessions and games when calculating the SHRZ TL to ensure greatest accuracy.